CHALLENGE FOR ASEAN-CHINA FREE TRADE AGREEMENT ON INDONESIA EMPLOYMENT - Riswati, Fatimah; Warsito, Indro (Economic Journal of Emerging Markets, 2011)
This research analyzes the challenges for Indonesian economy towards the implementation of ASEAN-China Free Trade Area (ACFTA) especially on employment opportunity in Indonesia. Using regression technique, the labour cost and change in fix capital are statistically significant in influencing the employment opportunity. This result implies that ACFTA will challenge the Indonesian competitiveness due to increasing labour cost, while ACFTA also potentially increases capital flow from China which has ambiguous impacts on labour absorption. The SWOT (Strength, Weakness, Opportunity and Threat) analysis recommends for Indonesian government to improve comprehensive strategy of national industry to be more competitive to China products. Keywords: ACFTA, employment opportunity, structural equation model JEL classification numbers: F13, F14, F15, F42